Efek Anti-Agregasi Platelet Ekstrak Etanol Daun Salam (Syzygium polyanthum (Wight) Walp.) pada Mencit - RIKA SARI DEWI; NI MADE DWI SANDHIUTAM; SULISTYO RAHARJO (Fakultas Farmasi Universitas Pancasila, 2013)
Salam leaves (Syzygium polyanthum (Wight) Walp.) contains fl avonoids, volatile oil and phenolic acid that can inhibiting platelet aggregation induced by ADP (adenosine diphospate), arachidonic acid, epinephrine, thrombin, collagen and aff ecting the activity enzyme ectonucleotidase so it can be used as anti-platelet drug. The purpose of this study was to investigated 70% ethanol extract of salam leaves have anti-platelet aggregation eff ect and increase of dose can also increase anti-platelet aggregation. This study was performed in 5 groups, each group consisted of 5 mice there were: groups of positive control, normal control, 70% ethanol extract leaves doses (150, 300, 450) mg/ kg, each group is given orally once daily during 8 days and measurements of parameters at day-0 and day-9th. The results of this study was 70% ethanol extract of leaves of salam leaves doses (150,300, 450) mg/kgBW showed the eff ects prolong bleeding time, coagulation time, enhance the decreased plasma absorbance after the addition of ADP. From the measurement parameter bleeding time, coagulation time and measurement decreased plasma absorbance after the addition of ADP that 70% ethanol extract of salam leaves doses 150, 300 and 450 mg/kgBW have anti-platelet aggregation eff ect and increase of dose was able to increase the eff ect anti-platelet aggregation.